Customary transfers and land sales in Côte d'Ivoire: revisiting the embeddedness issue - (:unkn) unknown (My University, 2010)
The article offers an empirical perspective regarding customary land sales in Côte d'Ivoire, focusing on their socio-political embeddedness as well as on the implications of such processes for the content of the rights and duties transferred. Two interlinked aspects of land transfers, which usually come together in African contexts, are to be taken into account: rights and obligations regarding land access and control ('the land resource dimension'), and rights and obligations regarding group membership, and more generally the socio-political dimensions that condition the social recognition and effectiveness of the transfer of land rights ('the socio-political dimension'). These two dimensions are empirically explored, together with the processes of their connection and possible disconnection/reconnection. We show that the diverging interpretations of land transfers, from emic as well as from etic viewpoints, do not necessarily correspond to mutually exclusive explanatory models, or to a simple transition phase from customary to 'pure' market land transfers. Access to land may become commoditized without extinguishing the socio-political dimension of land transactions. Another point is that the articulation of these two dimensions of land transfers is a specific and always contextualized issue. This has direct consequences on the legitimacy of land transfers as well as on the security of the stranger right holder within the local community and more generally on the politicization of land issue.
Keywords: African Research